Análisis de los hoteles de alta categoría de Croacia desde el enfoque hotel-huésped - Maja Šerić; Irene Gil Saura (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
The tourism sector of Croatia has been developing strongly in the last ten years. It is of crucial importance for its future development to be capable of managing the hotel sector according to the new market conditions. The purpose of this research is to study high-quality hotels of Croatia from the hotels' and guests' points of view focusing on a new marketing strategy named Integrated Marketing Communications (IMC), advancements in Information and Communication Technology (ICT), and loyalty. The findings show a high degree of IMC and ICT implementation and moderate degree of development of loyalty programs in hotels. Moreover, they confirm a positive influence of ICT on IMC implementation, as well as a positive impact of IMC on loyalty.
Keywords: M10; M31; 330; high-quality hotels; Croatia; integrated marketing communications; information and communication technology; loyalty.